2011
DOI: 10.1111/j.1365-2559.2011.03777.x
|View full text |Cite
|
Sign up to set email alerts
|

Salivary gland mucoepidermoid carcinoma is a clinically, morphologically and genetically heterogeneous entity: a clinicopathological study of 40 cases with emphasis on grading, histological variants and presence of the t(11;19) translocation

Abstract: The results underscore the great histological diversity of MEC, the reproducibility of the WHO grading criteria and the value of histological subtypes as an additional prognostic factor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
49
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(49 citation statements)
references
References 31 publications
0
49
0
Order By: Relevance
“…(5,6) CTCR1-MAML2 fusion has been detected in 40-80% of primary salivary gland mucoepidermoid carcinomas, and we and other research groups have shown that the fusion gene is associated with a distinct tumor subset with an indolent clinical course. (7)(8)(9)(10) Fehr et al (2008) report a novel fusion gene, CRTC3-MAML2, (11) and in Nakayama et al (12) we reveal that CRTC3-MAML2 fusion-positive mucoepidermoid carcinoma cases have an excellent prognosis. These findings suggest that both CRTC1-MAML2 and CRTC3-MAML2 fusions may be associated with mucoepidermoid carcinoma cases with favorable clinicopathological tumor features.…”
mentioning
confidence: 75%
“…(5,6) CTCR1-MAML2 fusion has been detected in 40-80% of primary salivary gland mucoepidermoid carcinomas, and we and other research groups have shown that the fusion gene is associated with a distinct tumor subset with an indolent clinical course. (7)(8)(9)(10) Fehr et al (2008) report a novel fusion gene, CRTC3-MAML2, (11) and in Nakayama et al (12) we reveal that CRTC3-MAML2 fusion-positive mucoepidermoid carcinoma cases have an excellent prognosis. These findings suggest that both CRTC1-MAML2 and CRTC3-MAML2 fusions may be associated with mucoepidermoid carcinoma cases with favorable clinicopathological tumor features.…”
mentioning
confidence: 75%
“…Fgf8 and Il6 are of greater importance than Areg or Tnfα. Schwarz et al, 2011). Although the precise etiology of MEC is largely unknown, we have recently shown that cytomegalovirus is an important component of MEC tumorigenesis (Melnick et al, , 2012.…”
Section: Discussionmentioning
confidence: 98%
“…Clear cells have been reported in benign tumors such as PA, myoepithelioma, and oncocytoma, and malignant tumors such as myoepithelial carcinoma, oncocytic carcinoma, MEC, AcCC, PLGA, and AdCC (1). Clear cells are commonly associated with MEC, with sporadic clear cell change reported in up to 30% of cases, but predominant clear cell change is rarer (2,11). AcCC has been shown to feature clear cell in approximately 6% of cases, but with predominant clear cell populations in only 1% (1).…”
Section: Discussionmentioning
confidence: 99%